Radiation protection: A guide for scientists, regulators, and physicians - Shapiro, Jacob (Harvard University, 2014)
This is a definitive guide to the safe use of radioactive materials. Completely revised and updated, the fourth edition covers of nonionising radiation, and is thus concerned with the entire field of radiation protection.